Smurfs [videorecording (Blu-Ray)] - Brady, Pam; Karliak, JP, 1981-; Levy, Daniel, 1983-; Sedaris, Amy; Lyonne, Natasha; Oh, Sandra, 1971-; Kimmel, Jimmy, 1967-; Spencer, Octavia; Kroll, Nick; Waddingham, Hannah, 1974-; Winter, Alex, 1965-; Erskine, Maya, 1987-; et al. (Paramount, 2025)
When Papa Smurf is taken by evil wizards Razamel and Gargamel, Smurfette leads the Smurfs on a mission to the real world to save him.